Applied sport management skills - Lussier, Robert N.; Kimball, David Charles 1959-
"Undergraduate-level text that provides students with a thorough understanding of the management principles used in sport organizations while also helping students developing their practical skills. The text is organized around the central management functions of planning, organizing, leading, and controlling"--Provided by publisher.
To the Student -- To the Instructor -- Part I Introduction to Sport Management -- Managing Sports -- The Sport Industry -- What Is Sport Management? -- What Does It Take to Be a Successful Manager? -- What Do Sport Managers Do? -- How Do Managers Differ? -- Learning Aids -- The Sport Industry Environment: Globalization, Ethics, and Social Responsibility -- Internal Environment and Quality in Sport -- External Environment -- Conducting Sport Business in a Global Environment -- Ethics in Sport Management -- Social Responsibility and Sustainability -- Learning Aids -- Part II Planning -- Creative Problem Solving and Decision Making -- An Overview of Problem Solving and Decision Making -- Step 1: Define the Problem or Opportunity -- Step 2: Set Objectives and Criteria -- Step 3: Generate Alternatives -- Step 4: Select the Most Feasible Alternative -- Step 5: Implement the Decision -- Step 6: Control the Results -- Learning Aids -- Strategic and Operational Planning -- An Overview of Strategic and Operational Planning -- Strategic Process -- Analysis of the Environment -- Setting of Objectives -- Corporate-Level Strategy -- Business-Level Strategy -- Functional-Level Strategies -- Implementing and Controlling the Strategies -- Learning Aids -- Part III Organizing -- Organizing and Delegating Work -- The Organizing Function -- Authority -- Organizational Design -- Job Design -- Organizing Yourself and Delegating Work -- Learning Aids -- Sport Culture, Innovation, and Diversity -- Managing Change -- Organizational Culture -- Innovation, Quality, and the Learning Organization -- Diversity -- Organizational Development -- Learning Aids -- Human Resources Management -- Human Resources Management Process and Department -- Legal Environment -- Human Resources Planning and Job Design -- Attracting Employees -- Interviewing -- Developing Employees -- Performance Appraisals -- Retaining Employees -- Learning Aids -- Part IV Leading -- Behavior in Organizations: Power, Politics, Conflict, and Stress -- Organizational Behavior and Thoughts -- Personality -- Perception -- Attitude Formation and Behavior -- Power -- Politics in the Office and on the Field -- Managing Conflict -- Negotiation -- Collaboration -- Stress -- Learning Aids -- Team Development -- Importance of Teamwork to Performance -- Group Performance Model -- Group Structure -- Group Process -- Stages of Group Development and Leadership Styles -- Developing Groups Into Teams -- Getting to Better Meetings -- Learning Aids -- Communicating for Results -- Understanding the Importance of Good Communication -- Using Organizational Communication -- Using Interpersonal Communication -- Using the Channels -- Sending Messages -- Receiving Messages -- Responding to Messages -- Dealing With Emotions and Criticism -- Learning Aids -- Motivating to Win -- Motivation and Performance -- Content-Based Motivation Theories -- Process- Based Motivation Theories -- Reinforcement Theory -- Putting Theory to Work Within the Motivational Process and Motivating Yourself -- Learning Aids -- Leading to Victory -- Leadership -- Behavior of Effective Leaders -- Contemporary Behavioral Perspectives -- Situational Leadership Theories and Models -- Getting to Your Personal Style of Leadership -- Learning Aids -- Part V Controlling -- Controlling Quality, Financials, and Productivity, and Managing People -- Quality and Control Systems -- Control Process -- Frequency of Controls -- Financial Controls -- Managing People -- Managing Problem Employees -- Productivity -- Learning Aids -- Facilities and Events Management -- Sport Facilities and Event Management -- Sport Facilities Management -- Sport Event Management -- Planning and Controlling Sports -- Sales Forecasting Techniques -- Scheduling Tools -- Time Management -- Learning Aids -- Afterword: The Future of Balance in Sport -- Appendix: Careers in Sport Management
MSSalazar (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Sports administration